Medication Adherence of Patients with Pemphigus and Bullous Pemphigoid Disorders in a Tertiary Care Teaching Hospital – A Prospective-Observational Study - James, Jerin; Sadasivan, Jayakrishnan; George, Anuja Elizabeth (Journal of Pharmacy Practice and Community Medicine)
Background: Pemphigus and Bullous Pemphigoid are auto-immune blistering diseases. Management of these chronic and severe conditions requires various modes of prolonged therapy. Therefore, medication adherence has a very important and essential role in treating these disorders. Objectives: The goal of the research was to assess the medication adherence of patients with Pemphigus and Bullous Pemphigoid and to correlate it with the quality of life of these patients. Methods: A ‘prospective, observational’ study was conducted in the ‘Department of Dermatology and Venereology’, in a tertiary care centre from December 2019 to June 2020. A sample of 28 patients was enrolled in the study. Medication adherence was calculated by using the ‘Morisky Green Levine medication adherence scale’. Quality of life was evaluated by using ‘Dermatology Life Quality Index’. Results: The 28 patients were aged between 24 and 82 years with a mean of 52.61±15.247 years. Majority of patients (82.1%) belonged to the High Adherence group, while 14.3% of the patients belonged to the Moderate adherence group and only 3.6% of patients belonged to the Low medication adherence group. The initial quality of life (DLQI 1) of patients had a mean score of 14.11±4.508 and the quality of life of the same patients after 3 months (DLQI 2) had a mean score of 4.86±4.897. A statistically significant relationship between the quality of life and adherence to medication was observed in this study. Conclusion: High adherence to medication was seen in most patients.
Keywords: Pemphigus; Corticosteroid therapy; Quality of life; Medication Adherence; Dermatology Life Quality Index.